Tingkat Produktivitas Karyawan, Profesionalisme Kerja dan Kompensasi terhadap Kinerja Karyawan - Jesslyn Tanri; Sanly Dewi; Eric Andriyo; Jimmy S (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine and analyze the effect of employee productivity levels, work professionalism, and compensation on employee performance at PT. Surya Tara Jaya. This research method is descriptive quantitative. The sampling method uses saturated sampling technique. The sample of this research is all employees of PT. Surya Tara Jaya as many as 55 people. Statistical method using Multiple Linear Regression Analysis, by testing the hypothesis test statistic t. The results showed, a) the employee productivity variable has a value of tcount < ttable, namely -2.227 < -2.008 and a significant 0.030 > 0.05; b) the variable of work professionalism has a value of tcount > ttable, namely 4.38 > 2.008 and a significant value of 0.00 <0.05; c) the compensation variable has a tcount <ttable, namely 0.87 <2.008 and a significant 0.389 > 0.05. In conclusion, employee productivity has a partial and significant effect on employee performance at PT. Surya Tara Jaya. Work professionalism has a partial and significant effect on the performance of employees at PT. Surya Tara Jaya. Compensation has no effect and is not partially significant on the performance of employees at PT. Surya Tara Jaya. Employee productivity, work professionalism, and compensation have a significant and simultaneous effect on employee performance at PT. Surya Tara Jaya. Keywords: Employee Performance, Compensation, Employee Productivity, Work Professionalism